DW Cancri in X-rays. Issue 3 (16th January 2019) - Nucita, A A; Conversi, L; Licchelli, D
ABSTRACT: We report on the XMM – Newton observation of DW Cnc, a candidate intermediate polar candidate whose historical optical light curve shows the existence of periods at ≃38, ≃86, and ≃69 min, which were interpreted as the white dwarf spin, the orbital and the spin–orbit beat periodicities. By studying the 0.3–10 keV light curves, we confirm the existence of a period at ≃ 38 min and find in the OM light curve a signature for a period at 75 ± 21 min, which is consistent with both the orbital and spin–orbit beat. These findings allow us to unveil without any doubt, the nature of DW Cnc as an accreting intermediate polar. The EPIC and RGS source spectra were analysed and a best-fitting model, consisting of a multitemperature plasma, was found. The maximum temperature found when fitting the data is kT max ≃ 31 keV, which can be interpreted as an upper limit to the temperature of the shock.